Adverse childhood experiences and behavioral problems in early adolescence: An empirical study of chinese children - Chen, Yunfan (Frontiers in Psychiatry, 2022)
The aim of the present study was to examine the relationships between ACEs and behavioral problems of children in their early adolescence in Chinese society. Results from bivariate analyses of 2,910 Chinese children in early adolescence indicated that children begin to exhibit behavioral problems being related to the exposure of adverse childhood experiences (ACEs). Compared to those with 0 ACEs, children with 4 or more ACEs were 4.45 times (p < 0.001), 4.44 times (p < 0.001), 7.80 times (p < 0.001), 4.49 times (p < 0.001), and 6.63 times (p < 0.001) more likely to demonstrate hyperactivity, peer communication problems, pro-social problems, emotional problems and conduct problems, respectively. Rural children, children of mothers with low education, and boys were particularly likely to have been exposed to multiple categories of ACE. This study evidenced that there was a strong association between exposure to ACEs and behavioral problems in early adolescence in China.